Employer branding for SMEs: Attracting graduating students in IT industry - Ruey Komulainen (OrdnungsPolitisches Portal (OPO), 2015)
Employer Branding has been an emerging topic in HRM for less than two decades. The concept of Employer Branding is a popular recruitment strategy used by large companies or MNCs. However, researches on the effectiveness of Employer Brand-ing for SMEs are very limited. Thus, this research aims to study the role of Employer Branding in SMEs, especially IT SMEs in Finland. This research focused on the perspectives of graduating students, the prospective employees of SMEs, as the main research targets. The theoretical framework is developed using concepts of Marketing (Lievens and Highhouse (2003)) and Strategic HRM (Barney 1991) and how they are connected within Employer Branding. Quantitative survey is utilised and 181 good responses were collected. The empirical findings suggest that employer branding has positive influence on students' decision to apply for a job in SMEs but on the contrary, the correlation between instrumental and symbolic values of the employer branding to the attitude of the prospective student employees is weak. The study suggests that although Employer Branding is a widely used approach to attract prospective employees by large companies, this concept may not be as effective if applied by the SMEs in the Finnish IT industry.
Keywords: 330; IT SMEs; Employer Branding; graduating students